Intradermal actions of hypertonic saline involve neural and vascular mechanisms. - Sharara, A M (1995)
The aim of this study was to investigate whether the wheal and flare responses to intradermal injection of hypertonic (4.5%) saline (HTS) were inhibited by local injection of 1% lignocaine. Eight normal subjects were studied on one occasion. Lignocaine (0.125 ml) was infiltrated at four sites on one forearm and normal saline on the other. Five minutes later, duplicate intradermal injections of 30 microliters of histamine (22.5 nmol ml-1), substance P (1 nmol ml-1), HTS and normal saline were given coded and in random order, one of each pair to each forearm. Lignocaine inhibited flare responses to histamine, substance P and HTS by 56% (P < 0.01), 78% (P < 0.01) and 77% (P < 0.05) respectively suggesting similar involvement of an axon reflex. Wheal to histamine was inhibited by 31% (P < 0.02) and to substance P by 33% (P < 0.05) but not to HTS. This suggests that the mechanism of wheal response to HTS differs from that of histamine and substance P.